The semantics of Rudin constructions in Romanian - Caponigro, Ivano; F˘ăl˘ăus, Anamaria (Proceedings of the Amsterdam Colloquium, 2022)
We broaden the empirical and formal landscape of wh-constructions by describing and analyzing an understudied non-interrogative wh-construction requiring multiple wh expressions, to which we refer as the ‘Rudin construction’. We argue that, unlike other multiple wh-constructions studied to date, Rudin constructions are biclausal and should be semantically analyzed as establishing identity between the extensions of two relations.